The mediating role of learning motivation: An integrated TAM2 and self-determination theory model for e-learning achievement - Yuliati, Emi; Rujianto, Eko; Karyono, Giat (STAI Auliaurrasyidin Tembilahan, 2026)
Prior research based on the Technology Acceptance Model 2 (TAM2) has largely emphasized technological and social factors while offering limited insight into how learner motivation translates system acceptance into meaningful learning outcomes. To address this gap, this study integrates TAM2 core constructs, namely Perceived Ease of Use, Perceived Usefulness, and Social Influence, with key motivational drivers, including hedonic, intrinsic, and extrinsic motivation, to examine their combined effects on behavioral intention, learning motivation, and learning achievement in e-learning contexts. Data were collected from 300 e-learning users using a Likert-scale questionnaire and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results reveal that Perceived Ease of Use strongly influences Perceived Usefulness (β = 0.611, p < 0.001), indicating that simplifying system usability is fundamental for users to recognize the value of e-learning platforms. Perceived Usefulness and Social Influence significantly predict behavioral intention, while motivational factors collectively exert a substantial effect on learning motivation, which in turn strongly enhances learning achievement (β = 0.552, p < 0.001). The proposed model explains a substantial proportion of variance in learning motivation (64%) and learning achievement (55%), demonstrating good predictive relevance within the studied context. Mediation analysis further confirms that learning motivation serves as a key mechanism through which technology acceptance and motivational factors translate into improved learning outcomes. A key practical implication is that e-learning designers should prioritize not only system usefulness and ease of use but also hedonic elements that enhance enjoyment, as this jointly foster learning motivation and ultimately drive learning achievement.